Technologies and materials for renewable energy, environment and sustainability. (November 2020) - Salame, Chafic-Touma
Abstract: "TMREES Conference Series: Technologies and Materials for Renewable Energy, Environment and Sustainability" aim to promote sustainable, healthy and diverse ecosystems; encourage & support the Sustainability and development of security systems through green-based & clean resources, bringing together participants from international organizations, universities, industry & administrative to exchange innovative ideas, explore enabling technologies, share experiences in sustainability issues & to open a new window on the circumstances of the classical energy sources & their harmful impact on the society.